The dimensions of food insecurity and malnutrition among people living with HIV in Senegal, West Africa. Issue 12 (2nd December 2017) - Benzekri, Noelle A.; Sambou, Jacques F.; Diaw, Binetou; Sall, El Hadji Ibrahima; Sall, Fatima; Niang, Alassane; Ba, Selly; Guèye, Ndèye Fatou Ngom; Diallo, Mouhamadou Baïla; Hawes, Stephen E.; Seydi, Moussa; Gottlieb, Geoffrey S.
ABSTRACT: An understanding of the factors contributing to food insecurity and malnutrition among people living with HIV (PLHIV) in Senegal is urgently needed in order to develop effective interventions. The goals of this study were to identify differences in the dimensions of food security among PLHIV in Dakar versus Ziguinchor, Senegal, to determine which of these dimensions are most predictive of severe food insecurity, and to identify factors associated with malnutrition. We conducted a cross-sectional study at outpatient clinics in Dakar and Ziguinchor, Senegal. Data were collected using participant interviews, anthropometry, the Household Food Insecurity Access Scale, the Individual Dietary Diversity Scale, and chart review. Interviews were conducted with ninety-five food insecure, HIV-infected subjects. Daily household income and daily food expenditure per household member were the strongest predictors of severe food insecurity. The practice of agriculture, livestock ownership, nutritional status, and HIV outcomes were not predictive of severe food insecurity. CD4 count <350/mm 3 was the strongest predictor of malnutrition. Severe food insecurity, daily household income, daily food expenditure per household member, dietary diversity score, skipping meals, the practice of agriculture, livestock ownership, ART status, and adherence were not predictive of malnutrition. This is the first study to analyze the dimensions of food security among PLHIV in Senegal. We discovered important differences in food access, availability, stability, and utilization in Dakar versus Ziguinchor. We found that economic access was the strongest predictor of severe food insecurity and poorly controlled HIV was the strongest predictor of malnutrition. Our findings suggest that the interventions needed to address food insecurity differ from those necessary to target malnutrition, and that effective interventions may differ in Dakar versus Ziguinchor. Furthermore, this study highlights a need for a greater understanding of the relationship between HIV and malnutrition among individuals receiving ART in resource-limited settings.